Phase Angle From Bioelectrical Impedance for the Assessment of Sarcopenia in Cirrhosis With or Without Ascites - Ruiz-Margáin, Astrid; Xie, Jesse J; Román-Calleja, Berenice M; Pauly, Margaret; White, Michelle G; Chapa-Ibargüengoitia, Mónica; Campos-Murguía, Alejandro; González-Regueiro, José A; Macias-Rodríguez, Ricardo U; Duarte-Rojo, Andres (Clinical gastroenterology and hepatology, 2021)
Skeletal muscle index (SMI) from computed tomography (CT) reliably assesses sarcopenia, however, it is expensive and involves serial radiation exposure. Phase angle (PhA) from bioimpedance analysis (BIA) is a noninvasive, low cost, bedside nutritional tool used to monitor changes to nutritional interventions. We aimed to compare the performance of PhA with SMI to assess sarcopenia in cirrhosis. Ambispective cohort study. Consecutive patients with cirrhosis and available images from abdominal CT scan were included. Monofrequency BIA was performed within 2 weeks CT. Spearman's correlation, ROC curve, and survival analysis with Kaplan-Meier, Cox and competing-risk regression were performed. 136 patients were included with a mean age of 54.5 years (60% female). Most had decompensated disease (66%) with ascites in 47%, and a mean MELD of 14 ± 6. We found positive correlations between SMI and PhA (r = 0.58 , P < .001), irrespective of the presence of ascites. The AUROC of PhA-sarcopenia in all patients was 0.702; (0.748 in males,0.677 in females). The best cutoffs of PhA for diagnosing sarcopenia were ≤5.6° in males and ≤5.4° in females. SMI and PhA were significantly associated with survival in Kaplan-Meier curves. In multivariable analyses, SMI was outperformed by age and MELD, whereas PhA remained independently associated with mortality. Considering transplantation as a competing risk, regression analysis showed both SMI and PhA to be independent predictors of mortality (sHR:0.95 [0.90-0.99] and sHR:0.61 [0.42-0.88]). PhA moderately correlates with SMI for the identification of sarcopenia in patients with cirrhosis. However, its prognostic accuracy is comparable to that of SMI, and it is not influenced by ascites.